Brain‐Based Learning and Educational Neuroscience: Boundary Work. Issue 1 (March 2015) - Edelenbosch, Rosanne; Kupper, Frank; Krabbendam, Lydia; Broerse, Jacqueline E. W.
ABSTRACT Much attention has been given to "bridging the gap" between neuroscience and educational practice. In order to gain better understanding of the nature of this gap and of possibilities to enable the linking process, we have taken a boundary perspective on these two fields and the brain‐based learning approach, focusing on boundary‐spanning actors, boundary objects, and boundary work. In 26 semistructured interviews, neuroscientists and education professionals were asked about their perceptions in regard to the gap between science and practice and the role they play in creating, managing, and disrupting this boundary. Neuroscientists and education professionals often hold conflicting views and expectations of both brain‐based learning and of each other. This leads us to argue that there are increased prospects for a neuroscientifically informed learning practice if science and practice work together as equal stakeholders in developing and implementing neuroscience research.